The potential of therapeutic garden in promoting student wellbeing / Muhammad Hazim Asraf Mohamad Mustafa Albakri and Marina Abdullah - Mohamad Mustafa Albakri, Muhammad Hazim Asraf; Abdullah, Marina (2024)
This research paper explores the therapeutic potential, specifically by healing gardens, in promoting physical and mental wellbeing among students in educational institutions, as well as in other institutional settings such as healthcare facilities, rehabilitation centres, and residential. A review of relevant literature suggests that therapeutic gardens can offer numerous benefits, including stress reduction, improved mood, and increased social interaction, as well as therapeutic properties of the plants used in the gardens, such as reducing anxiety, improving memory, and promoting relaxation. The design of therapeutic gardens, with features such as water elements and walking paths, can also contribute to their therapeutic potential. Educational institutions should prioritize the accessibility and effectiveness of these gardens, ensuring that all students have equal access to their benefits, while healthcare facilities and other institutions should also consider incorporating healing gardens as a therapeutic intervention for promoting physical and mental wellbeing among their residents or patients. To summarize, therapeutic gardens are a promising intervention for improving health and wellbeing in institutional settings. Further research is needed to fully understand their potential and effectiveness especially among institution community.